2023
DOI: 10.1002/anie.202304611
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Formation of Macrocycles for Efficient Crystallization of 2D Covalent Organic Frameworks with Enhanced Photocatalytic Hydrogen Evolution

Abstract: Covalent organic frameworks (COFs) have gained significant attention as key photocatalysts for efficient solar light conversion into hydrogen production. Unfortunately, the harsh synthetic conditions and intricate growth process required to obtain highly crystalline COFs greatly hinder their practical application. Herein, we report a simple strategy for the efficient crystallization of 2D COFs based on the intermediate formation of hexagonal macrocycles. Mechanistic investigation suggests that the use of 2,4,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…High-resolution transmission electron microscopy (HRTEM) further revealed that TADI-COF and TADI-COF-Fc nanoparticles are both generated by the aggregation of small, thin flakes with sizes of approximately 15 nm. This finding was consistent with the coherent scattering domain size calculated from the PXRD patterns using the Debye–Scherrer equation . Lattice-resolution HRTEM images were obtained and subjected to fast Fourier transform (FFT) and band-pass filtering analysis, which showed that TADI-COF and TADI-COF-Fc exhibited interplanar spacings of 3.1 and 3.2 nm, respectively.…”
Section: Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…High-resolution transmission electron microscopy (HRTEM) further revealed that TADI-COF and TADI-COF-Fc nanoparticles are both generated by the aggregation of small, thin flakes with sizes of approximately 15 nm. This finding was consistent with the coherent scattering domain size calculated from the PXRD patterns using the Debye–Scherrer equation . Lattice-resolution HRTEM images were obtained and subjected to fast Fourier transform (FFT) and band-pass filtering analysis, which showed that TADI-COF and TADI-COF-Fc exhibited interplanar spacings of 3.1 and 3.2 nm, respectively.…”
Section: Results and Discussionsupporting
confidence: 81%
“…This finding was consistent with the coherent scattering domain size calculated from the PXRD patterns using the Debye−Scherrer equation. 67 Lattice-resolution HRTEM images were obtained and subjected to fast Fourier transform (FFT) and band-pass filtering analysis, which showed that TADI-COF and TADI-COF-Fc exhibited interplanar spacings of 3.1 and 3.2 nm, respectively. These values are consistent with the (100) interplanar spacing (3.2 nm).…”
Section: Resultsmentioning
confidence: 99%
“…24). 143 Notably, under visible light irradiation with AA as the SED, 3 wt% Pt-loaded COF-935 showed excellent photocatalytic H 2 evolution activity up to 67.55 mmol g −1 h −1 . The effect of different Pt loadings on hydrogen production was further investigated.…”
Section: Factors That Influence the Photocatalyst Activitymentioning
confidence: 98%
“…For instance, high-crystalline COF-935 was rapidly synthesized based on the formation of hexagonal intermediates (Figure 5b). 36 The dynamic imine bond helped to maintain the reversibility of COF formation, which provided an opportunity for the modification and reconstruction of the framework. As a result, when it was exposed to visible light, COF-935 exhibited extremely high hydrogen evolution up to 67.55 mmol • g −1 • h −1 with 3 wt% Pt as a cocatalyst.…”
Section: Optimization Of Ordered Structurementioning
confidence: 99%